Orthodox Christianity and Gender Dynamics of Tradition, Culture and Lived Practice - Kupari, Helena; Vuola, Elina (Taylor & Francis, 2019)
The Orthodox Christian tradition has all too often been sidelined in conversations around contemporary religion. Despite being distinct from Protestantism and Catholicism in both theology and practice, it remains an underused setting for academic inquiry into current lived religious practice. This collection, therefore, seeks to redress this imbalance by investigating modern manifestations of Orthodox Christianity through an explicitly gender-sensitive gaze. By addressing attitudes to gender in this context, it fills major gaps in the literature on both religion and gender. Starting with the traditional teachings and discourses around gender in the Orthodox Church, the book moves on to demonstrate the diversity of responses to those narratives that can be found among Orthodox populations in Europe and North America. Using case studies from several countries, with both large and small Orthodox populations, contributors use an interdisciplinary approach to address how gender and religion interact in contexts such as, iconography, conversion, social activism and ecumenical relations, among others. From Greece and Russia to Finland and the USA, this volume sheds new light on the myriad ways in which gender is manifested, performed, and engaged within contemporary Orthodoxy. Furthermore, it also demonstrates that employing the analytical lens of gender enables new insights into Orthodox Christianity as a lived tradition. It will, therefore, be of great interest to scholars of both Religious Studies and Gender Studies.